An interface treatment method for improving the energy dissipation effect of rubber concrete

By subjecting rubber concrete to water treatment, NaOH treatment and zinc stearate treatment, the problem in the existing technology that the rubber concrete's vibration damping performance is improved but its compressive strength is reduced is solved, achieving a significant improvement in its vibration reduction while taking into account the basic performance. vibration performance.

CN116573873BActive Publication Date: 2025-01-21SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310507817.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-05
Publication Date
2025-01-21
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

The prior art is difficult to improve the vibration damping performance of rubber concrete while taking into account its basic properties, such as compressive strength.

Method used

Through interface treatment methods such as water treatment, NaOH treatment and zinc stearate treatment, the strength and damping ratio of the interface zone of rubber concrete are improved, thereby improving its vibration reduction performance.

Benefits of technology

While ensuring that the compressive strength of rubber concrete is not reduced, its vibration damping performance is significantly improved, effectively reducing the vibration impact caused by urban rail transit operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116573873B_ABST
    Figure CN116573873B_ABST
Patent Text Reader

Abstract

The present invention relates to an interface treatment method for improving the energy consumption effect of rubber concrete, including a water washing treatment, a NaOH treatment and a zinc stearate treatment method performed in sequence. The water washing treatment is to rinse the rubber particles in clean water, fully soak them for 2-3 hours and dry them; the NaOH treatment is to wash the rubber particles in clean water, fully soak them in a NaOH solution of a certain concentration for 2-5 hours and dry them; the zinc stearate treatment is to mix the rubber particles treated with NaOH and dried with a certain amount of zinc stearate powder after determining the amount of zinc stearate powder added, and place them in a shaking sieve machine for 5-10 minutes to make them fully and evenly mixed. The present invention solves the pollution and recycling problems of waste rubber tires, while improving the damping ratio of rubber concrete, effectively improving the vibration reduction performance of rubber concrete, and on this basis, taking into account its basic performance such as strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an interface treatment method for improving the energy consumption effect of rubber concrete, belonging to the technical field of interface treatment. Background Art

[0002] With the continuous expansion of rail transit demand and operating mileage, passengers waiting for trains and residents along the line are easily affected by train vibrations due to the arrival and departure of trains, which affects their daily work and life and even endangers their health. At the same time, precision instruments and key cultural relics along the line are also sensitive to train vibrations, and the demand for vibration reduction is increasing.

[0003] At the same time, with the growing demand for sustainable development of infrastructure, the treatment of waste materials has received increasing attention. Due to the development of economy and urban transportation, the number of cars has continued to increase, and with it comes the pollution problem of a large number of waste rubber tires. Adding rubber to concrete can not only effectively deal with this problem, but also improve the durability and toughness of concrete to a certain extent. At the same time, rubber concrete has good vibration reduction and isolation performance, and has significant advantages in engineering applications. It can effectively reduce the impact of vibration generated by train operation on surrounding residents and buildings.

[0004] The vibration reduction performance of rubber concrete is mainly related to the replacement content of rubber particles. Generally speaking, the more rubber content is added within a certain range, the better the vibration reduction performance of rubber concrete may be. However, the continuous addition of rubber content will reduce the basic properties of rubber concrete, such as compressive strength, and thus affect its practical application in engineering. At present, there is no corresponding measure that can effectively improve the vibration reduction performance of rubber concrete while taking into account its basic performance. Summary of the invention

[0005] The present invention provides an interface treatment method for improving the energy dissipation effect of rubber concrete, which improves the overall vibration reduction performance of the concrete structure and effectively reduces the impact of vibration generated by urban rail transit operation while ensuring the basic performance of the rubber concrete, such as the strength.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] An interface treatment method for improving the energy dissipation effect of rubber concrete specifically comprises the following steps:

[0008] Step S1: water treatment, weighing rubber particles of a preset weight, washing the dust on the surface of the rubber particles with clean water, and soaking the rubber particles washed with clean water in water until the surface of the rubber particles is fully in contact with the water;

[0009] Step S2: After the rubber particles are completely soaked in clean water, they are taken out, the surface is cleaned and laid flat to dry;

[0010] Step S3: NaOH treatment, preparing a NaOH solution of a preset concentration, and immersing rubber particles weighing a preset weight in the NaOH solution until the surface of the rubber particles is fully in contact with the NaOH solution;

[0011] Step S4: After the rubber particles are completely soaked in the NaOH solution, they are taken out and rinsed with clean water until the pH value of the solution for rinsing the rubber particles is weakly acidic;

[0012] Step S5: cleaning the surface of the rinsed rubber particles and laying them flat to dry;

[0013] Step S6: zinc stearate treatment, adding a matching weight of zinc stearate powder to the rubber particles weighed with a preset weight, and fully mixing the rubber particles and the zinc stearate powder until the zinc stearate powder is evenly attached to the surface of the rubber particles;

[0014] As a further preferred embodiment of the present invention, in step S1, the rubber particles washed with clean water are soaked in water for 2-3 hours and stirred every 15 minutes;

[0015] As a further preferred embodiment of the present invention, in step S2, the rubber particles are spread out to dry until the rubber particles are wrapped with a paper towel and the paper towel is squeezed hard, and the surface of the paper towel is not wet;

[0016] As a further preferred embodiment of the present invention, in step S3, the rubber particles are immersed in the NaOH solution for 2-5 hours and stirred every 15 minutes until some of the rubber particles floating on the surface of the NaOH solution are also fully in contact with the NaOH solution;

[0017] As a further preferred embodiment of the present invention, in step S4, after the rubber particles are taken out from the NaOH solution, they are rinsed with clean water for 5-10 minutes, and the pH value of the solution after rinsing the rubber particles is tested with a pH test paper until the pH value stabilizes at 6.5-7.5;

[0018] As a further preferred embodiment of the present invention, in step S5, the rubber particles are spread out to dry until the rubber particles are wrapped with a paper towel and the paper towel is squeezed hard, and the surface of the paper towel is not wet;

[0019] As a further preferred embodiment of the present invention, in step S6, determining the amount of zinc stearate powder to be added specifically comprises the following steps:

[0020] Step S61: weighing 100 g of rubber particles treated with NaOH and dried;

[0021] Step S62: adding 1-3 g of zinc stearate powder, placing in a shaker and mixing for 5-10 minutes, weighing the entire weight of the rubber particles, and calculating the weight of zinc stearate attached to the surface of the rubber particles;

[0022] Step S63: repeating steps S61-S62 for several times, and calculating the average weight of zinc stearate attached to the surface of the rubber particles for several times, the average weight value x is the weight of zinc stearate required to be added per 100g of rubber particles;

[0023] Step S64: The weight of the weighed rubber particles and the weight of the added zinc stearate are calculated according to the following formula:

[0024]

[0025] In the above formula, m is the mass of zinc stearate added, M is the mass of rubber particles weighed, and x is the mass of zinc stearate required to be added per 100g of rubber particles;

[0026] As a further preferred embodiment of the present invention, in step S6, the rubber particles and the zinc stearate powder are placed in a sieve shaker and fully mixed for 5-10 minutes until the zinc stearate powder is evenly attached to the surfaces of all the rubber particles.

[0027] Through the above technical solution, compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The interface treatment method for improving the energy consumption effect of rubber concrete provided by the present invention, in which waste tire rubber particles are added when preparing rubber concrete, solves the environmental pollution and recycling problems of waste rubber products;

[0029] 2. The interface treatment method for improving the energy dissipation effect of rubber concrete provided by the present invention can improve the strength of the interface area through water washing treatment, NaOH treatment and zinc stearate treatment in sequence. The low-strength interface can increase the friction loss of the interface, thereby improving the damping ratio of the rubber concrete, and can also make up for the partial strength loss of the rubber concrete due to the use of rubber aggregates instead of sand and gravel aggregates;

[0030] 3. The interface treatment method for improving the energy dissipation effect of rubber concrete provided by the present invention is simple to operate and easy to implement. It improves the vibration reduction performance of rubber concrete while ensuring that the toughness of rubber aggregate is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0032] Figure 1 It is the time history curve of the rubber concrete beam only subjected to water washing treatment provided by the present invention;

[0033] Figure 2 It is the time history curve of the rubber concrete beam treated with NaOH only provided by the present invention;

[0034] Figure 3It is the time history curve of the rubber concrete beam treated only with zinc stearate provided by the present invention. DETAILED DESCRIPTION

[0035] The present invention will now be described in further detail with reference to the accompanying drawings.

[0036] As described in the background technology, the research premise of this application is that it is hoped that waste tires can be mixed into concrete to make rubber concrete, which can not only solve the problem of waste material recycling and pollution, but also improve the vibration reduction performance of concrete due to the durability and toughness of rubber itself. However, if the content of rubber cannot be reasonably controlled, the compressive strength of rubber concrete will be reduced.

[0037] In order to improve the overall vibration reduction performance of the concrete structure without excessively reducing the strength of the rubber concrete (i.e. maintaining the compressive strength of the concrete itself), the present application provides an interface treatment method for improving the energy dissipation effect of the rubber concrete. The method obtains a low-strength interface through a specific interface treatment method, thereby increasing the friction loss of the interface, thereby improving the damping ratio of the rubber concrete, and further improving the vibration reduction of the rubber concrete. Of course, the vibration reduction of the rubber concrete is improved, but the compressive resistance of the concrete itself is not reduced. Specifically, the following steps are included:

[0038] Step S1: water treatment, weighing a preset weight of rubber particles, washing the dust on the surface of the rubber particles with clean water, soaking the rubber particles washed with clean water in water for 2-3 hours, and stirring every 15 minutes until the surface of the rubber particles is fully in contact with the water.

[0039] Step S2: After the rubber particles are completely soaked in clean water, they are taken out, the surface is cleaned and they are laid flat to dry, until the rubber particles are wrapped with a paper towel and the paper towel is squeezed hard, and the surface of the paper towel is not wet.

[0040] Step S3: NaOH treatment: prepare a NaOH solution of a preset concentration, soak rubber particles weighing a preset weight in the NaOH solution for 2-5 hours, and stir every 15 minutes until some of the rubber particles floating on the surface of the NaOH solution are also fully in contact with the NaOH solution.

[0041] Step S4: After the rubber particles are completely immersed in the NaOH solution, they are taken out and rinsed with clean water for 5-10 minutes. The pH value of the solution after rinsing the rubber particles is tested using a pH test paper until the pH value stabilizes at 6.5-7.5.

[0042] Step S5: Clean the surface of the rinsed rubber particles and lay them flat to dry until the rubber particles are wrapped with a paper towel and the paper towel is squeezed hard, and the surface of the paper towel is not wet.

[0043] Step S6: zinc stearate treatment, adding a matching weight of zinc stearate powder to the rubber particles weighed with a preset weight, and placing the rubber particles and the zinc stearate powder in a shaking sieve machine to be fully mixed for 5-10 minutes until the zinc stearate powder is evenly attached to the surface of the rubber particles.

[0044] When zinc stearate treatment is performed, it is necessary to determine the mass relationship between zinc stearate powder and rubber particles. In this application, the zinc stearate powder that needs to be added to 100g of rubber particles is used as the benchmark. The method for obtaining this benchmark is:

[0045] Step S61: weighing 100 g of rubber particles treated with NaOH and dried;

[0046] Step S62: adding 1-3 g of zinc stearate powder, placing in a shaker and mixing for 5-10 minutes, weighing the entire weight of the rubber particles, and calculating the weight of zinc stearate attached to the surface of the rubber particles;

[0047] Step S63: Repeat steps S61-S62 for several times, and calculate the average weight of zinc stearate attached to the surface of rubber particles for several times. The average weight value x is the weight of zinc stearate required to be added per 100g of rubber particles.

[0048] After obtaining the average weight value x, proceed to step S64: the weight of the weighed rubber particles and the weight of the added zinc stearate are calculated according to the following formula:

[0049]

[0050] In the above formula, m is the mass of zinc stearate added, M is the mass of rubber particles weighed, and x is the mass of zinc stearate required to be added per 100g of rubber particles. Thus, the actual weight of zinc stearate matching the weight of rubber particles is obtained.

[0051] The biggest advantage of this application is that the concrete is treated with water, NaOH and zinc stearate in sequence to have the best vibration reduction performance and compressive strength, thereby effectively reducing the impact of vibration generated by urban rail transit operations without excessively reducing the basic properties of rubber concrete such as strength.

[0052] Next, according to the interface treatment method provided by the present application, a matching embodiment is given to verify the excellence of the present application. In this example, water washing treatment is as follows: first weigh 150g of rubber particles, rinse with clean water for three minutes to wash away surface dust and other impurities, and then soak the rubber particles in water for 2 hours after washing, and stir every 15 minutes to ensure that the surface of the rubber particles is in full contact with water.

[0053] NaOH treatment: first prepare a 5% mass fraction NaOH solution, weigh 300g rubber particles, soak them in the NaOH solution for 2 hours, and stir them every 15 minutes to make the particles floating on the surface of the solution fully contact with the NaOH solution. After soaking completely, take them out and rinse them with clean water for 5 minutes, and use pH test paper to test the pH value of the solution formed after rinsing. The measured value is about 6.9, which means that it is basically completely clean.

[0054] The zinc stearate treatment is completed on the basis of the NaOH treatment. Weigh 100g of rubber particles treated with NaOH, add 1g of zinc stearate, pour it into a sieve, the aperture of which is much smaller than the average particle size of the rubber particles but can allow the zinc stearate powder to pass through easily. After fully mixing, place it on a sieve shaker for 5 minutes, weigh the total mass of the rubber particles, and calculate the mass of zinc stearate attached to the surface of the rubber particles. Repeat the above work 3 times, and the average value of the mass of zinc stearate adsorbed on the surface of the particles is 0.4g, that is, the mass of zinc stearate required to be added for every 100g of rubber particles is 0.4g. Then carry out zinc stearate treatment: weigh 300g of rubber particles, add 1.2g of zinc stearate, mix the two thoroughly and place them on a sieve shaker for 5 minutes, so that the zinc stearate powder is evenly distributed on the surface of the rubber particles.

[0055] The rubber particles that have been washed, treated with NaOH, and treated with zinc stearate are made into rubber concrete beams with other coarse and fine aggregates, cement, etc. The size of the rubber concrete beam is 50mm×50mm×400mm. After the preparation is completed, the damping ratio of the rubber concrete beam is measured by the free decay method. The small beam is fixed in the chuck at one end in the form of a cantilever beam, and a sensor is set at the other end. A small hammer is used to hit the rubber concrete beam near the sensor to make it vibrate and decay freely. The corresponding vibration acceleration and other data are recorded by the sensor, and the damping ratio of the rubber concrete mixed with rubber particles with different interface treatments is calculated to evaluate its vibration reduction performance.

[0056] It should be noted that, for rubber concrete beams under different working conditions, in order to obtain a suitable damping ratio, water treatment, NaOH treatment and zinc stearate treatment are not required at the same time, and can be adjusted accordingly according to the actual working conditions. The damping ratio time history curve of the three treatment methods is given in the embodiment. The damping ratio of a rubber concrete beam treated with water is calculated to be 0.02323, and its time history curve is shown in FIG. Figure 1 As shown in the figure, the damping ratio of a rubber concrete beam treated with water and NaOH is calculated to be 0.02253, and its time history curve is shown in the figure. Figure 2 As shown in the figure, the damping ratio of a rubber concrete beam treated with water, NaOH and zinc stearate is 0.02680, and its time history curve is shown in the figure. Figure 3As shown; it can be seen that the damping ratio of the rubber concrete beam obtained by the interface treatment method provided by the present application is the largest, which improves the vibration reduction performance of the rubber concrete material.

[0057] When the damping ratio reflecting the vibration reduction of rubber concrete material is the largest, after the matching interface treatment, the modification effect of the rubber surface is also reflected by the changes in the rubber-mortar interface strength and fracture energy, that is, the rubber-mortar interface strength and fracture energy are both decreasing. After experimental verification, the rubber-mortar interface strength corresponding to water washing, NaOH, and zinc stearate are 142400Pa, 145620Pa, and 79560Pa, respectively, and the fracture energy is 19.39J / m 2 , 19.67J / m 2 , 10.48J / m 2 ,From the experimental data, the interface strength and fracture energy are consistent with the ,principle, showing a gradually decreasing trend.

[0058] Therefore, the pollution and recycling problems of waste rubber tires are solved, and at the same time the damping ratio of rubber concrete is improved, the vibration reduction performance of rubber concrete is effectively improved, and on this basis, its basic performance such as strength is taken into account.

[0059] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in common dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless defined as herein.

[0060] The meaning of "and / or" described in this application means that the situations where each exists alone or both exist at the same time are included.

[0061] The term “connection” as used in this application may mean a direct connection between components or an indirect connection between components via other components.

[0062] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. An interface treatment method for improving the energy dissipation effect of rubber concrete, characterized in that: The specific steps include: Step S1: water treatment, weighing rubber particles of a preset weight, washing the dust on the surface of the rubber particles with clean water, and soaking the rubber particles washed with clean water in water until the surface of the rubber particles is fully in contact with the water; Step S2: After the rubber particles are completely soaked in clean water, they are taken out, the surface is cleaned and laid flat to dry; Step S3: NaOH treatment, preparing a NaOH solution of a preset concentration, and immersing rubber particles weighing a preset weight in the NaOH solution until the surface of the rubber particles is fully in contact with the NaOH solution; Step S4: After the rubber particles are completely soaked in the NaOH solution, they are taken out and rinsed with clean water until the pH value of the solution for rinsing the rubber particles is weakly acidic; Step S5: cleaning the surface of the rinsed rubber particles and laying them flat to dry; Step S6: zinc stearate treatment, adding a matching weight of zinc stearate powder to the rubber particles weighed with a preset weight, and fully mixing the rubber particles and the zinc stearate powder until the zinc stearate powder is evenly attached to the surface of the rubber particles; Wherein, in step S6, determining the amount of zinc stearate powder to be added specifically comprises the following steps: Step S61: weighing 100 g of rubber particles treated with NaOH and dried; Step S62: adding 1-3 g of zinc stearate powder, placing in a shaker and mixing for 5-10 minutes, weighing the entire weight of the rubber particles, and calculating the weight of zinc stearate attached to the surface of the rubber particles; Step S63: repeating steps S61-S62 for several times, and calculating the average weight of zinc stearate attached to the surface of the rubber particles for several times, the average weight value x is the weight of zinc stearate required to be added per 100g of rubber particles; Step S64: The weight of the weighed rubber particles and the weight of the added zinc stearate are calculated according to the following formula: In the above formula, m is the mass of zinc stearate added, M is the mass of rubber particles weighed, and x is the mass of zinc stearate required to be added per 100 g of rubber particles.

2. The interface treatment method for improving the energy dissipation effect of rubber concrete according to claim 1, characterized in that: In step S1, the rubber particles washed with clean water are soaked in water for 2-3 hours and stirred every 15 minutes.

3. The interface treatment method for improving the energy dissipation effect of rubber concrete according to claim 2 is characterized in that: In step S2, the rubber particles are spread out to dry until the rubber particles are wrapped with a paper towel and the paper towel is squeezed hard, and the surface of the paper towel is not wet.

4. The interface treatment method for improving the energy dissipation effect of rubber concrete according to claim 1, characterized in that: In step S3, the rubber particles are immersed in the NaOH solution for 2-5 hours and stirred every 15 minutes until some of the rubber particles floating on the surface of the NaOH solution are also fully in contact with the NaOH solution.

5. The interface treatment method for improving the energy dissipation effect of rubber concrete according to claim 4, characterized in that: In step S4, after the rubber particles are taken out from the NaOH solution, they are rinsed with clean water for 5-10 minutes, and the pH value of the solution after rinsing the rubber particles is tested with a pH test paper until the pH value stabilizes at 6.5-7.

5.

6. The interface treatment method for improving the energy dissipation effect of rubber concrete according to claim 5, characterized in that: In step S5, the rubber particles are spread out to dry until the rubber particles are wrapped with a paper towel and the paper towel is squeezed hard, and the surface of the paper towel is not wet.

7. The interface treatment method for improving the energy dissipation effect of rubber concrete according to claim 1, characterized in that: In step S6, the rubber particles and the zinc stearate powder are placed in a shaker and fully mixed for 5-10 minutes until the zinc stearate powder is evenly attached to the surface of all the rubber particles.